2015
DOI: 10.59410/racyt-v04n01ep03-0047
|View full text |Cite
|
Sign up to set email alerts
|

Suplementación de fibra prebiótica en la elaboración de jamón prensado

Abstract: El objetivo del trabajo fue evaluar el jamón prensado suplementado con fibra prebiótica con niveles de 0.5, 1.0 y 1.5% (peso). Para esto se analizaron muestras de jamones suplementados y un testigo sin fibra prebiótica. Se valoraron los niveles de humedad, grasa, proteína, pH, ceniza, elementos no nitrogenados (ELNN) y características organolépticas de sabor a jamón, sabor dulce, color rosado, olor a jamón y textura compacta o aterciopelada en el producto final. La suplementación de fibra prebiótica en el jamó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The concentrations of citric, lactic, and fumaric acids determined in this study are consistent with those reported in the literature, with variations possibly attributed to differences in cacao variety and cultivation factors. The percentage of total acids quantified (1.41% w/w) is within the range of acidity percentages reported for CME by other researchers (Guirlanda et al ., 2021; Vallejo Torres et al ., 2016). These findings contribute to the characterisation of the organic acid profile of CME and can aid in assessing its suitability for use in various applications.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of citric, lactic, and fumaric acids determined in this study are consistent with those reported in the literature, with variations possibly attributed to differences in cacao variety and cultivation factors. The percentage of total acids quantified (1.41% w/w) is within the range of acidity percentages reported for CME by other researchers (Guirlanda et al ., 2021; Vallejo Torres et al ., 2016). These findings contribute to the characterisation of the organic acid profile of CME and can aid in assessing its suitability for use in various applications.…”
Section: Resultsmentioning
confidence: 99%